2003
DOI: 10.1590/s0080-62342003000300007
|View full text |Cite
|
Sign up to set email alerts
|

Ansiedade e mecanismos de coping utilizados por pacientes cirúrgicos ambulatoriais

Abstract: The goals of this study were to identify the anxiety state in surgical ambulatory patients in the pre-operative period, the coping mechanisms employed, their clinical manifestation, and to verify the influence of state anxiety during the pre-operative period. The results showed that 40 patients exhibited little anxiety and there was no significantly statistical correlation between preoperative anxiety state, coping mechanisms and clinical changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
4

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 5 publications
0
6
0
4
Order By: Relevance
“…A experiência prévia de um procedimento anestésico e cirúrgico e todas as suas implicações são vistas, portanto, como uma primeira exposição ao estressor, podendo influenciar nas estratégias de enfrentamento de outras cirurgias considerando seus níveis de complexidade 19 .…”
Section: Resultsunclassified
“…A experiência prévia de um procedimento anestésico e cirúrgico e todas as suas implicações são vistas, portanto, como uma primeira exposição ao estressor, podendo influenciar nas estratégias de enfrentamento de outras cirurgias considerando seus níveis de complexidade 19 .…”
Section: Resultsunclassified
“…The criteria for inclusion in the In other studies in a surgical service, showed that 97% of patients had some degree of anxiety, being touted as more frequently, the surgical procedure, the standby unit in the surgical procedure and the possibility of an pain and comfort. 19 Anxiety is a normal reaction to stress and threat or danger that can be caused by fear of death or disability. It usually occurs when an individual faces a change or the need to act differently than usual.…”
Section: Methodsmentioning
confidence: 99%
“…In all the periods in which anxiety was measured, the patients showed medium anxiety level, [21] characterized by scores ≥ 30 and ≤ 50. The average of STAI-state score-although not statistically significant-showed a decrease of 3.7 points between the preoperative and 45 days after surgery.…”
Section: Anxietymentioning
confidence: 99%